Rewriting the Myth: Costanza Casati’s Clytemnestra - Eiduka, Dina (Literatūra, 2025)
The rewriting of ancient myths has a deep historical tradition, as authors from antiquity to the modern era have reimagined mythical narratives to reflect their worldviews. Historically, these retellings often bore a masculine perspective, shaped by the authors’ gender and cultural context. The emergence of second-wave feminism in the twentieth century, however, marked a transformative shift, with women authors reclaiming mythic narratives to illuminate female experiences and challenge patriarchal constructs. This paper examines the evolving portrayal of Clytemnestra, a figure rooted in Homeric epics as the unfaithful wife and husband’s murderer but later reimagined through reception as a grieving mother destroyed by male ambition. Through the lens of matricentric feminism, this paper analyses the construction of Clytemnestra’s character in antiquity and its reception in Costanza Casati’s 2023 novel Clytemnestra, exploring how her depiction of Clytemnestra reconstructs the character’s identity for the twenty-first century audiences, with particular focus placed on her role as a mother.
Keywords: Clytemnestra; classical reception; myth rewriting; matrifocal narrative; matricentric feminism